Fehlordnungen im Aufbau kristalliner Stoffe, bestimmt aus Gitterkonstanten und Dichtemessungen - M. E. Straumanis (CHIMIA)
In this article a summary of tlie first attempts to détermine n' (the actual number of molecules per unit cell in contrast to n, which gives the number of molecules in an ideal or sound lattice) by precision determination of the volume v of the unit cell, of the macroscopie density d of the substance and of its molecular weight M is given. The calculations of n' were made using the well known equation n' = vdN0/M, where N0 is the Avogadro Number. The methods of determination of v, d and M from experimental measurements and the errors of these determinations are discussed. The total error connected with the computation of n’ and its significance is also mentioned.